Structural Equation Modeling to Construct Customer Behavioral Intentions in Japanese-Style Yakiniku Restaurants: A Case Study of the Umai Chain Brand - Chih-Wei Lin; Wen-Goang Yang; Wei-Yeng Sia; Yi-Ling Liu; Yu-Sheng Lin; Chen-Hsiang Hsieh (Engineering Proceedings)
By constructing a linear structural equation model, we explored the impact of the customer service, food quality, and physical environment on customer behavioral intentions with experiential value and customer satisfaction as mediators. We focused on customers of the renowned Taiwanese franchised restaurant, Umai Yakiniku, in the Taichung area, Taiwan, and its services. Through customer perception and experience, we unraveled the subsequent behavioral dynamics. A total of 337 valid questionnaires were collected through purposive sampling. The participants encompassed customers who had previously dined at the Umai Yakiniku restaurant, excluding those attending corporate events. The overall behavioral model of customers showed a satisfactory level of fit. The customer service, food quality, and physical environment significantly impacted the experiential value. Customer service directly impacted customer satisfaction, while food quality and the physical environment indirectly affected customer satisfaction. Experiential value positively impacted customer satisfaction, and customer satisfaction positively affected behavioral intentions. Such findings provide information for related companies and their strategic management.